Graduating during the COVID-19 pandemic: digital media practices and learning spaces among pupils taking their school-leaving exams - Mahlknecht, Belinda; Kempert, Richard; Bork-Hüffer, Tabea (Sustainability, 2022)
The COVID-19 pandemic has profoundly changed educational and qualification experiences among young people. When the pandemic spread in 2020, schools worldwide were required to switch to remote learning. Through a qualitative multi-method, partly mobile, in-situ research approach, we accompanied pupils in the final year of their secondary education as they prepared for and finalized their school-leaving exams to investigate the following questions: What did pupils’ socio-material-technological learning spaces look like during this period? How did they adapt their digital media practices to cope with learning remotely? How did their situatedness in these learning spaces influence their learning experiences? Building on existing research in the field of digital and children’s geographies as well as learning spaces, through a combined content and narrative analysis, this article situates pupils’ learning spaces and experiences of graduating during the pandemic in the context of family relations, socio-material home spaces, polymediated learning environments and the accessibility of outdoor spaces. We debate the wide spectrum of media practices—ranging from indulgence in digital media, to balanced media use, to attempting to withdraw from using digital media—used by pupils to navigate through inextricably entangled socio-material-technological spaces during the pandemic. The further digitization of education prompted by the pandemic must be used in ways that empower pupils to engage in responsible and active use of digital media, thus allowing them to become mature and resilient digital participants in society.
Gesehen am 10.04.2024